Legal Reconstruction of Input Tax Credits That Have No Direct Relationship With Business Activities For Legal Certainty of Corporate Taxpayers - Setiawan, Wisnu Paruly; Ismail, Ismail; Setiawan, Puguh Aji Hari (Ilmu Hukum Prima (IHP), 2026)
Taxes play a crucial role in national development, both as a source of state revenue and as an instrument for regulating the economy. Value Added Tax (VAT), with its Input Tax credit mechanism against Output Tax, is designed to maintain the principle of neutrality, but in practice it often raises legal issues. Article 9, paragraph 8, letter (b) of the VAT Law, concerning the phrase "directly related to business activities," lacks a clear definition, thus opening room for multiple interpretations. This has given rise to numerous disputes between Corporate Taxpayers and the Directorate General of Taxes (DGT). This research employs a normative legal method with a statutory, conceptual, and case-based approach. The results show that the norm in Article 9 paragraph 8 letter (b) has fundamental weaknesses due to multiple interpretations and implications for legal uncertainty. Legal reconstruction is needed through the development of an explicit negative list, consistent jurisprudence, and modern, digital-based administrative guidelines, so that the national tax system can provide legal certainty, protect taxpayer rights, and strengthen the principle of VAT neutrality. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan kasus. Bahan hukum primer yang digunakan meliputi Undang-Undang PPN, UU HPP, dan putusan pengadilan terkait, sedangkan bahan hukum sekunder berupa literatur perpajakan, jurnal, dan karya ilmiah yang relevan. Analisis dilakukan secara deduktif dengan interpretasi sistematis dan teleologis untuk menilai kesesuaian norma dengan asas legalitas, keadilan, serta tujuan sistem perpajakan. Hasil penelitian menunjukkan bahwa norma dalam Pasal 9 ayat 8 huruf (b) UU PPN memiliki kelemahan mendasar karena multitafsir dan berimplikasi pada ketidakpastian hukum. Putusan pengadilan memperlihatkan adanya penafsiran sempit dan formalis terhadap “hubungan langsung dengan kegiatan usaha,” yang merugikan Wajib Pajak Badan. Rekonstruksi hukum diperlukan melalui penyusunan daftar negatif (negative list) yang eksplisit, konsistensi yurisprudensi, serta pedoman administratif modern berbasis digitalisasi. Dengan demikian, sistem perpajakan nasional dapat memberikan kepastian hukum, melindungi hak Wajib Pajak, serta memperkuat prinsip netralitas PPN dalam mendukung iklim investasi dan pertumbuhan ekonomi.